2020
DOI: 10.1097/hpc.0000000000000234
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Education-based HEART Score Pathway on Coronary Computed Tomography Angiography Utilization and Yield in the Emergency Department

Abstract: Objective: There is a growing consensus to reduce unnecessary testing among low-risk chest pain patients. The objective of this study was to evaluate the impact of implementing an education-based HEART score pathway in the emergency department on coronary computed tomography angiography (CCTA) utilization and yield. Methods: A retrospective before and after intervention study was conducted at a single site. Adult emergency department patients undergoing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…These time periods allowed a matching comparison to the data obtained from the prior education-based HEART pathway implemented at our institution. 15 While we did not expect that time period would impact yield outcome, utilization outcome could vary by month. Hence, we chose the same 6 months for before and after periods in this study to ensure consistency.…”
Section: Study Setting and Populationmentioning
confidence: 92%
See 1 more Smart Citation
“…These time periods allowed a matching comparison to the data obtained from the prior education-based HEART pathway implemented at our institution. 15 While we did not expect that time period would impact yield outcome, utilization outcome could vary by month. Hence, we chose the same 6 months for before and after periods in this study to ensure consistency.…”
Section: Study Setting and Populationmentioning
confidence: 92%
“…Our previously conducted study showed that this approach failed to reduce CCTA utilization and did not improve the yield of obstructive CAD. 15 We believed this lack of effect was due to low use of HSs and the suggested algorithm.…”
Section: Importancementioning
confidence: 98%